2005
DOI: 10.1002/pmic.200401307
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic identification of differentially‐expressed genes in human gastric carcinomas

Abstract: Although genetic alterations in proto-oncogenes, tumor-suppressor genes, cell cycle regulators, and cell growth factors have been implicated in the process of human gastric carcinogenesis, the principle carcinogenic mechanisms are not fully understood. In this study, we used a proteomic approach to search for genes that may be involved in gastric carcinogenesis and that might serve as diagnostic markers. We identified nine proteins with increased expression and 13 proteins with decreased expression in gastric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(80 citation statements)
references
References 43 publications
3
76
1
Order By: Relevance
“…All of the carcinoma specimens were histologically diagnosed as advanced carcinoma. They found CYR61 protein was down-regulated in gastric carcinoma tissues as compared with normal gastric mucosae (45). The discrepancy between that study and the current one might be due to different study design.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…All of the carcinoma specimens were histologically diagnosed as advanced carcinoma. They found CYR61 protein was down-regulated in gastric carcinoma tissues as compared with normal gastric mucosae (45). The discrepancy between that study and the current one might be due to different study design.…”
Section: Discussioncontrasting
confidence: 45%
“…It has recently been reported that CYR61 is down-regulated in a proteomics analysis study in human gastric carcinomas using two-dimensional gel studies, independent of antibody (45). In that study, the authors used a proteomic approach to search for genes that may be involved in gastric carcinogenesis and that might serve as diagnostic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Although this point remains unclear, our study underscores a possible link between the acetylation status of tubulin and entry to chromosome condensation. In this context, it is notable that our previous proteomic studies found that the expression of a group of tubulin-related proteins is altered in gliomas or gastric carcinomas in comparison to normal tissues (Hiratsuka et al, 2003;Nishigaki et al, 2005). Although SIRT2 as a novel mitotic checkpoint protein T Inoue et al how CHFR contributes to mitotic checkpoints is not fully understood, several mechanisms of CHFR function have been proposed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, all spots with differing intensity between normal and GC tissue were rechecked in 8 pairs of 2-DE images from each sample pair, to identify those with a high incidence rate. A significant difference in the expression of a protein between tumor and normal tissue was defined as >2-fold change in spot density in >30% of tumor specimens (9).…”
Section: Protein Separation By Two-dimensional Gel Electrophoresis (2mentioning
confidence: 99%